Effect of Various Plasticizers in Different Concentrations on Physical, Thermal, Mechanical, and Structural Properties of Wheat Starch-Based Films - A. B. A. Mohammed, Abdulrahman; Hasan, Zaimah; A. Borhana Omran, Abdoulhdi; M. Elfaghi, Abdulhafid; Khattak, M.A.; Ilyas, R. A.; Sapuan, S. M. (Mdpi, 2023)
Biocomposite materials are essential for environmental protection, as they have the ability of substituting synthetic plastic with natural materials. This work investigated how different plasticizers (Glycerol (G), Fructose (F), Sorbitol (S), and Urea (U)) affect the morphological, mechanical, thermal, and physical characteristics of films made of wheat starch at various concentrations (0%, 15%, 25%, and 35%). Plasticizers were added to improve the flexibility and homogeneity of the wheat starch-based bioplastic. Control film exhibited high tensile strength (38.7 MPa) with low elongation (1.9%). However, films plasticized with 35% sorbitol showed the highest elongation, which was 60.7% at break. At 35% of all plasticizers, fructose showed the highest tensile strength, with 7.6 MPa. The addition of different plasticizers shows improvement in water resistance; films plasticized with glycerol had the lowest water absorption at 35% fructose (187.4%) and also showed coherent surfaces. Glycerol, sorbitol, and urea films showed a higher mass loss compared to fructose films. Fructose showed the highest performance after the analysis of the results, with low water absorption, water content, and mass loss and with high mechanical performance at 35% of fructose. SEM images show that the addition of fructose and glycerol improves the surface homogenate, while sorbitol and urea have a less compact structure with large pores.